Effect of Ciprofloxacin Administration on Gastric Histopathological Changes in Mice - Lisa Savitri; Kharisul Ihsan; Rochmad Krissanjaya; Elfred Rinaldo Kasimo; Novirma Yanti; Mochamad Hanif Hilmi (Biology, Medicine, & Natural Product Chemistry, 2025)
Ciprofloxacin is a fluoroquinolone antibiotic widely used in clinical and veterinary practice. While effective against a broad range of bacterial infections, several studies have reported potential adverse effects on the gastrointestinal tract, particularly the gastric mucosa. This study aimed to evaluate the histopathological changes in the gastric mucosa of mice following ciprofloxacin administration at different doses. A total of 24 male mice were randomly divided into four groups: control, low-dose ciprofloxacin, moderate-dose ciprofloxacin, and high-dose ciprofloxacin. Treatment was administered orally for 14 days. Gastric tissues were collected and examined histologically using hematoxylin-eosin staining. Histopathological analysis revealed dose-dependent mucosal alterations. The control group showed intact gastric architecture, while the low-dose group exhibited mild epithelial erosion. The moderate-dose group presented with mucosal disruption and inflammatory infiltration, and the high-dose group demonstrated severe ulceration, edema, and mucosal thinning. These findings indicate progressive gastric injury with increasing ciprofloxacin exposure. Ciprofloxacin administration induces dose-dependent gastric mucosal injury in mice, consistent with fluoroquinolone-related gastrointestinal toxicity. Caution is warranted in prolonged or high-dose therapy, and further studies are needed to explore the underlying mechanisms and potential gastroprotective interventions.